2019
DOI: 10.1155/2019/7132861
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Diabetic Foot Ulcers and Lower Extremity Amputations in Three Selected Tertiary Hospitals in Ghana

Abstract: Background. The occurrence and complications of diabetes are increasing worldwide. This study examined the prevalence and determinants of diabetic foot ulcers and lower extremity amputations in three selected tertiary hospitals in Ghana. Methods. A cross-sectional multicenter study involving 100 subjects was carried out. Subjects were selected through simple random sampling from three selected tertiary hospitals in Ghana. A structured questionnaire was used to document information on sociodemographic, medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
4
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 36 publications
6
49
4
5
Order By: Relevance
“…Totally 336 patients participated in this study. The mean ± SD age was 55.9±12.5 years, showing that our study population is largely middle aged, which is in keeping with findings from other studies (Atosona and Larbie 2019;Djibril et al 2018;Saleem et al 2017). About 96% of the patients in this study had type 2 diabetes, similar to findings from other studies, which reported type 2 diabetes as the commonest type of diabetes (Mehmood et al 2008;Pemayun and Naibaho 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Totally 336 patients participated in this study. The mean ± SD age was 55.9±12.5 years, showing that our study population is largely middle aged, which is in keeping with findings from other studies (Atosona and Larbie 2019;Djibril et al 2018;Saleem et al 2017). About 96% of the patients in this study had type 2 diabetes, similar to findings from other studies, which reported type 2 diabetes as the commonest type of diabetes (Mehmood et al 2008;Pemayun and Naibaho 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Sixty-seven percent (66) of the new diabetes-related LEA patients had one or more medical complications indicating a need for specialised services. The above findings show a much lower rate of diabetes-related LEA than the 3% prevalence reported from three tertiary hospitals in Ghana [16] and the overall rate of major amputation of 11.1% reported from a retrospective review of medical records of consecutive type 2 diabetes patients referred for diabetes management to King Abdullah University Hospital (KAUH) in the period between January 2014 and December 2015 [17]. Several different studies have reported rates of 2%-16% [18].…”
Section: Discussionmentioning
confidence: 56%
“…There were, however, other studies that showed insignificant correlation between smoking and risk of diabetic foot problem. 18,19 This study has shown that duration of diabetes more than 10 years had one-time risk of developing foot at risk. This is again was similar to a study done by Che Ahmad (2012) whereby the prevalence of foot at risk is higher in diabetic with duration more than 10 years (59.9%).…”
Section: Awareness and Practice Levelmentioning
confidence: 90%